The Principal's Managerial Role in Increasing Parental Participation in the Quality of Kalongan 02 Ungaran Public Elementary School - Ari Teliti Wilarsati; Nurkolis Nurkolis; Ali Shodiqin (Jurnal Pendidikan Terapan, 2026)
Purpose: This study was motivated by the gap between the standards outlined in KSP 2024 and the actual conditions in schools, as well as parental participation that remains limited to formal activities and has not yet developed into an active partnership between schools and families. The study aimed to analyze the principal’s planning, organizing, implementation, and supervision in encouraging parental participation toward school quality at SD Negeri Kalongan 02. Methods: This research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, then analyzed using an interactive model consisting of data reduction, data presentation, and conclusion drawing. Data validity was tested through technique and source triangulation. Findings: The findings indicate that planning is carried out systematically and participatively through needs identification, deliberation, and open socialization. Organization is carried out through teacher placement based on competency, strengthening coordination, and developing partnerships with parents. Implementation is realized through participatory learning, continuous teacher development, open communication, and parental involvement in school activities. Supervision is carried out systematically through academic supervision, teacher performance evaluation, monitoring of learning activities, and regular coordination meetings to ensure the achievement of school quality standards. This study concludes that school management based on participatory leadership makes a positive contribution to improving the quality of education through systematic planning, effective organization, collaborative implementation, and continuous supervision. Research Implications: This study implies that school quality improvement can be strengthened through participatory principal leadership, effective communication, teacher development, and active parental involvement in school programs. Originality: This study is original in examining parental participation through the principal’s managerial functions within the KSP 2024 framework, emphasizing active school-family partnerships in improving school quality.